Phytochemical Constituents and Antioxidant Activity of Oudneya Africana L. Leaves Extracts: Evaluation Effects on Fatty Acids and Proteins Oxidation of Beef Burger during Refrigerated Storage - Hafedh Hajlaoui; Soumaya Arraouadi; Hedi Mighri; Mouna Chaaibia; Néji Gharsallah; Gaspar Ros; Gema Nieto; Adel Kadri (MDPI AG, 2019)
Five Oudneya Africana (OA) leaves extracts were screened for their total phenolic (TPC), total flavonoid (TFC), condensed tannins (CTC) content, as well as their antioxidant capacity. The highest amount of TPC (661.66 ± 0.08 mg GAE/g), TFC (344.68 ± 0.44 mg QE/g) and TCT (90.18 ± 0.49 mg CE/g) was recorded to ethanol, acetone, and dichloromethane extracts, respectively. For 2,2-diphenyl-1-picrylhydrazyl (DPPH) (22.00 ± 0.03 µg/mL) and Reducing Power Assay (FRAP) (269.00 ± 0.01µg/mL) assays, ethanol extract showed the potent activity, while with ABTS test, acetone extract was the most active (761.15 ± 0.09 µg/mL). HPLC-MS analysis of acetonic and ethanolic extracts reveals the predominance of quinic acid, chlorogenic acid, 4-O-caffeoylquinic acid, and rutin compounds. The addition effect evaluation of OA extracts in beef burger preservation demonstrates the powerful effect (p < 0.05) of acetonic and ethanolic ones (0.03%) to inhibit lipids oxidation during storage for 10 days, given by the lowest increase in Thiobarbituric Acid-reactive Substances (TBARS) values as compared to the (−) control with a significant difference between free thiols values. In addition, these two extracts appear to be effective (p < 0.05) for pH stability, color, and sensory parameters as compared to (+) and (−) controls and aqueous extract. Hamburger odour was considered as a dependent variable in multiple linear regression analysis, where the models results showed that physicochemical parameters determine more burger odour than sensorial ones.